Early-onset parkinsonism caused by alpha-synuclein gene triplication: Clinical and genetic findings in a novel family. Issue 8 (August 2015) - Olgiati, Simone; Thomas, Astrid; Quadri, Marialuisa; Breedveld, Guido J.; Graafland, Josja; Eussen, Hubertus; Douben, Hannie; de Klein, Annelies; Onofrj, Marco; Bonifati, Vincenzo
Abstract: Introduction: Triplications of SNCA, the gene encoding for α-synuclein, cause a very rare Mendelian form of early-onset parkinsonism combined with cognitive and autonomic dysfunctions. Only six families with SNCA triplications have been described so far, limiting our knowledge of the associated phenotype. In this study, we report clinical and genetic findings in a new Italian family with SNCA triplication. Methods: The patients' phenotype was assessed by neurological examination, neuropsychological tests, and brain imaging (MRI and SPECT-DaTSCAN). For the genetic investigation, we used three independent techniques: genome-wide SNP microarrays, fluorescence in situ hybridization (FISH), and multiplex ligation-dependent probe amplification (MLPA). Results: Genetic studies documented the presence of four copies of the SNCA gene in the affected family members. FISH experiments and the segregation in the family were consistent with a heterozygous triplication of the SNCA locus. The patients carrying the SNCA triplication developed early-onset parkinsonism combined with depression, behavior disturbances, sleep disorders, and cognitive decline; marked autonomic dysfunctions were not observed. Brain imaging revealed fronto-parietal atrophy and a severe striatal dopaminergic deficit. Conclusion: The identification of this novel family contributes to the genetic and clinical characterization of this rare form. Our data reinforce the view that SNCA triplications cause early-onset parkinsonism, with prominent non-motor features. Highlights: We report a SNCA triplication in a novel family, the seventh reported so far. The SNCA triplication was confirmed using three independent genetic techniques. Patients developed early-onset parkinsonism with behavioral and cognitive deterioration. Our work contributes to the clinical and genetic characterization of this form of parkinsonism.